A creep control for distributed rear wheel drive bus. (December 2020) - Wang, Yuan; Yuan, Liangxin; Chen, Hao; Du, Peng; Lian, Xiaomin
Creep control is a kind of start-up control for electric vehicle. In the paper, two closed-loop control is contained in the creep control strategy. Proportional control with torque limitation, which adjusts vehicle speed, is the outer-loop control; and anti-slip control is the inner-loop control. In this way, the vehicle speed indicates no overshoot and has uniform convergence with driving torque. Moreover, the vehicle can start up on low adhesion or split road, and the driver can control the creep speed by the brake pedal only, so that the driver's operation is reduced. Subjective evaluation method is proposed to determine the control performance metrics, and then the mathematical relationship between the performance metrics and the control parameters is established. The tuning method of the control parameters is proposed according to those performance metrics, which mitigates the workloads of calibration and provides a better driving experience. Some simulations and real vehicle experiments are conducted to verify that the control strategy has an expected performance.